2001
DOI: 10.1002/1097-0045(20010301)46:4<327::aid-pros1040>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the orphan nuclear receptor ROR? induces growth arrest in androgen-independent DU 145 prostate cancer cells

Abstract: BACKGROUND RORα is a transcription factor which belongs to the family of orphan nuclear receptors. The regulatory functions of this receptor are still poorly understood. However, response elements for RORα are present on the promoter of cell cycle‐related genes suggesting that it might be involved in the control of cell proliferation. In this study, we investigated the expression and the possible function of RORα in a human androgen‐independent prostate cancer cell line (DU 145). The thiazolidinedione‐derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 32 publications
(35 reference statements)
1
30
2
Order By: Relevance
“…8a). 33 AA stimulated PC3 cell growth, although at a higher dose (5 ϫ 10 Ϫ6 M) than that required to increase DU 145 cell proliferation (Fig. 8b).…”
Section: Experiments In Pc3 Cellsmentioning
confidence: 91%
See 1 more Smart Citation
“…8a). 33 AA stimulated PC3 cell growth, although at a higher dose (5 ϫ 10 Ϫ6 M) than that required to increase DU 145 cell proliferation (Fig. 8b).…”
Section: Experiments In Pc3 Cellsmentioning
confidence: 91%
“…28 We have shown previously that the ROR␣ family is expressed in DU 145 prostate cancer cells. 33 Experiments have now been carried out to identify the specific isoform of the orphan nuclear receptor that might be present in these cells. By RT-PCR, we have observed that only one cDNA band, corresponding to the ROR␣1 cDNA, was present in DU 145 cells (Fig.…”
Section: Expression Of the Ror␣1 Isoform In Du 145 Cellsmentioning
confidence: 99%
“…RORα has been reported in vitro to affect proliferation and differentiation of DU145 cells (Moretti et al 2001). It also been reported to reduce the invasiveness of prostate cancer cells (Moretti et al 2002).…”
Section: Retinoic Acid Receptor-related Orphan Receptor (Ror α/β/γ Ormentioning
confidence: 98%
“…Prostate [69] RORb RORc Liver X receptor-like (NR1H) LXRa Prostate [87], Breast [190], Colon [191], Pancreas [192], Esophageal [193], Liver [194] …”
Section: Pparamentioning
confidence: 99%
“…A number of putative natural and synthetic ligands have been identified that target RORs; most notably cholesterol, cholesterol metabolites and oxysterols that have been shown to bind to the LBD of RORs and induce conformational changes that affect coregulator interactions [66,67]. While recent research has focused on the therapeutic value of inhibiting RORs for treating metabolic and autoimmune diseases, analyses of published gene expression data indicate that RORa is downregulated in multiple cancers including prostate, breast and pancreatic cancer, and suggest that RORa may act as a tumor suppressor [66,[68][69][70].…”
Section: Rar-related Orphan Receptors (Rors) Nr1fmentioning
confidence: 99%